Ikonografi Dan Makna Penggambaran Arca Gaṇeśa Ekapāda Koleksi Museum Nasional Indonesia - Adwina, Radila; Ashari, Chaidir (PURBAWIDYA, 2025)
Abstract Among more than 160 Gaṇeśa statues found in Indonesia, only one is depicted in a standing position on one leg. Based on the positional form, this Gaṇeśa statue with inventory number 198 of the National Museum of Indonesia collection can be referred to as Gaṇeśa ekapāda. Several previous studies have shown differences of opinion in identifying the depiction. This study attempts to clearly identify the depiction and meaning of Gaṇeśa ekapāda by using iconographic and semiotic approaches. In the iconographic analysis, the statue is described based on its distinctive attributes and positional form. The depiction is then compared with ancient Hindu texts and with other Hindu-Buddhist statues and reliefs. The ekapāda position more closely depicts a form of severe austerities. From Peirce's semiotic perspective, this statue functions as a sign that has two main referents through icon and index associations. The resulting layers of meaning show that this statue has a complex symbolic meaning. The statue of Gaṇeśa ekapāda can be interpreted to represent Gaṇeśa as the giver of boons to his followers who practice discipline and perseverance in worship. In addition, this study also explores the relation of this statue to the social and religious dynamics in ancient Javanese society.